(untitled) (Research, Society and Development, 2022)
Tomato is one of the most cultivated vegetables in Brazil, there are several varieties and production systems, so that there are no low yields in crops it is necessary to ensure the water requirement of the culture. The objective of this work was to determine the demand and water footprint of table tomato based on the simulation of crops for the municipality of Paranapuã-SP at different times of the year. The municipality of Paranapuã-SP was established as the study area, climatic data were obtained from the UNESP CLIMA Channel. The simulations of planting times were performed using the CROPWAT 8.0 software. The water demand of tomatoes per cycle is higher considering planting in January (347.3 mm) and lower when planting in April (263.8 mm), the blue water footprint increases as planting is postponed, depending on the need to supply the water demand of the crop with the application of water via irrigation.